Pengaruh Akuntansi Pertanggungjawaban, Partisipasi Anggaran, Dan Kejelasan Sasaran Anggaran Terhadap Kinerja Hotel Berbintang Di Kabupaten Buleleng - Nyoman Agus Mahapradnya; I Putu Hendra Martadinata (Universitas Pendidikan Ganesha, 2023)
This study aims to test whether responsibility accounting, budget participation, and clarity of budget targets affect the performance of star hotels in Buleleng Regency. This type of research is a quantitative research. The population in this study were all managers working in 15 star hotels in Buleleng Regency. The samples were selected using a purposive sampling technique and a total of 68 samples were obtained. The data obtained were then analyzed using multiple regression analysis. The results of the study show that (1) responsibility accounting has a positive effect on hotel performance. (2) budget participation has a positive effect on hotel performance, (3) budget target clarity has a positive effect on hotel performance, and (4) responsibility accounting, budget participation, and budget target clarity have a simultaneous effect on hotel performance. This shows that responsibility accounting, budget participation, and clarity of budget targets can affect the performance of star hotels in Buleleng Regency. This research is expected to contribute to academic studies regarding responsibility accounting, budget participation, and clarity of budget targets on hotel performance. For the hotel management, it is expected to utilize the results of this research as a consideration in improving hotel performance by providing education and training, developing measurable performance standards, enhancing communication between management and employees, setting clear and specific target goals, conducting regular evaluations, and ensuring clear communication regarding the budget goals of the hotel.